Extraction of Soil Nutrients Using Mehlich-3 Reagent for Acid-Mineral Soils of Florida - Rao Mylavarapu; Tom Obreza; Kelly Morgan; George Hochmuth; Vimala Nair; Alan Wright (EDIS)
Soil testing is a multistep process starting with the collection of a sample that adequately represents the area or field to be tested. Due to wide-ranging soil conditions across Florida and the United States, multiple soil test methods exist. During the 1970s, Florida along with several other southeastern US states adopted Mehlich-1 (M1) as the official extractant for acidic soils. The UF/IFAS Plant Nutrient Oversight Committee approved the change from M1 to M3 in 2010. Based on observations of the interpretations, the technical committee revised the M3 interpretation in March 2014. The new interpretations have been correlated with the M1 interpretations, as closely and realistically as possible, so the actual nutrient recommendations are not changed. This 7-page fact sheet was written by Rao Mylavarapu, Tom Obreza, Kelly Morgan, George Hochmuth, Vimala Nair, and Alan Wright, and published by the UF Department of Soil and Water Science, May 2014.